2020
DOI: 10.1155/2020/8029721
|View full text |Cite
|
Sign up to set email alerts
|

Development of MicroRNAs as Potential Therapeutics against Cancer

Abstract: MicroRNAs (miRNAs) are small noncoding RNAs that function at the posttranscriptional level in the cellular regulation process. miRNA expression exerts vital effects on cell growth such as cell proliferation and survival. In cancers, miRNAs have been shown to initiate carcinogenesis, where overexpression of oncogenic miRNAs (oncomiRs) or reduced expression of tumor suppressor miRNAs has been reported. In this review, we discuss the involvement of miRNAs in tumorigenesis, the role of synthetic miRNAs as either m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 142 publications
0
43
0
Order By: Relevance
“…Over the past decade it has become clear that miRs are differentially expressed in many human malignancies [ 11 , 26 ] and associated with stage, progression, and metastasis of cancer [ 27 ]. Understanding the underlying mechanisms of miR dysregulation in malignant cells, that include chromosomal aberrations, changes in transcriptional control, epigenetic changes, and defects in the miR biogenesis pathway, is important to develop therapeutical anti-cancer strategies [ 28 ].…”
Section: Mechanisms Of Mir Dysregulation In the Tmementioning
confidence: 99%
See 2 more Smart Citations
“…Over the past decade it has become clear that miRs are differentially expressed in many human malignancies [ 11 , 26 ] and associated with stage, progression, and metastasis of cancer [ 27 ]. Understanding the underlying mechanisms of miR dysregulation in malignant cells, that include chromosomal aberrations, changes in transcriptional control, epigenetic changes, and defects in the miR biogenesis pathway, is important to develop therapeutical anti-cancer strategies [ 28 ].…”
Section: Mechanisms Of Mir Dysregulation In the Tmementioning
confidence: 99%
“…In line with PEI, cationic dendrimers, consisting poly(amidoamine) (PAMAM) or poly(propylenimine) (PPI) are delivering conjugated nucleic acids efficiently. Additionally, its comparatively low toxicity, biodegradability, and biocompatibility makes PAMAM preferable over PEI [ 27 ]. An even safer possibility are neutral Poly(lactide-co-glycolide) (PLGA) particles, which show no toxicity, but also a lower miR binding capacity.…”
Section: Delivery Of Mir Therapeuticsmentioning
confidence: 99%
See 1 more Smart Citation
“…MicroRNA is emerging as a next generation cancer treatment [41][42][43][44]. Studies showed that miR-1291 had anti-tumor effects in multiple cancers including renal cancer, esophagus cancer, pancreatic cancer, and prostate cancer [31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, many diseases have been associated with changes in the expression level of miRNAs, including systemic rheumatic diseases, nervous system disorders, sepsis, cardiovascular disease and different type of cancers such as breast, ovarian, cervical forms (Ceribelli et al, 2011;Abd-Aziz et al, 2020;Ali Syeda et al, 2020;Condrat et al, 2020). In addition, several investigations have recently demonstrated changes in circulating miRNAs in response to different infectious diseases, increasing the possibility for a new diagnostic tool (Acuña et al, 2020;Tribolet et al, 2020), even before the pathogen could be directly distinguished and prior to the onset of seroconversion (Stewart et al, 2013;Biswas et al, 2019).…”
Section: Mirnas and Diseasesmentioning
confidence: 99%